Dormancy in laboratory-reared Asian longhorned beetles, Anoplophora glabripennis. (April 2021) - Torson, Alex S.; Lei Zhang, Meng; Smith, Adam J.; Mohammad, Lamees; Ong, Kevin; Doucet, Daniel; Roe, Amanda D.; Sinclair, Brent J.
Graphical abstract: Abstract: An insect's capacity to survive winter is critical for range expansion in temperate regions. The Asian longhorned beetle ( Anoplophora glabripennis ) is a polyphagous wood-boring insect native to China and the Korean peninsula and poses a high risk of invasion in North America and Europe. It is unclear whether A. glabripennis enters diapause, which means that diapause cannot be included in assessments of the risk of this species invading forests in temperate regions. Using a laboratory colony, we examine larval developmental arrest, metabolic rates, gas exchange patterns, thermal sensitivity, and body composition to characterize larval dormancy. Chilled larvae entered a temperature-independent developmental arrest which usually required more than four weeks of chilling to break, decreased their metabolic rate by as much as 63%, and maintained energy stores throughout the chilling period – results consistent with an obligate diapause. We also observed a switch to discontinuous gas exchange at low temperatures. Thermal sensitivity of metabolic rate did not differ between chilled and non-chilled larvae. Taken together, we conclude that A. glabripennis enters a larval diapause during chilling and terminates diapause after a requisite chilling period. These results will enhance our ability to predict phenology and potential distribution of current and future invasions of A. glabripennis .